Comparison of Fascia Iliaca Block with Intravenous Paracetamol, as Postoperative Analgesic Method for Femur Surgery - Praveen kumar Shekhrajka; Dhaval kumar C Patel (Academia Anesthesiologica International, 2020)
Background: Postoperative pain is extremely unpleasant which causes severe discomfort to the patient as well as it increases the anxiety, hospital stay so overall total burden. Objectives: Comparison of efficacy between fascia iliaca block with intravenous paracetamol, as postoperative analgesic method after femur surgery. Simultaneously requirement of other analgesics in the first 24 hours.Subjects and Methods:Prospective longitudinal study conducted in patients belonging to age group of 18 to 65 years posted for femur surgeries. All patients were received Intrathecal injection of 3.5 ml of 0.5% hyperbaric bupivacaine and divided into two groups. After completion of surgery Group I received the Fascia Iliaca block with thirty ml of 0.25% of injection bupivacaine and Group II received injection Paracetamol one gram intravenously. Duration of analgesia, time from block / iv PCM to 1st rescue analgesia, number of patients as well as total doses of required rescue analgesics in 1st 24 hours were observed postoperatively.Results:From One hour onwards at all the time interval, mean pain scores was less in FIB group as compared to PCM group(p<0.001). In FIB group 15 (42%) patients had more than 24 hours and 11(32%) patients had 12-24 hours of analgesia, where as in PCM Group not a single patient had more than 12 hours of analgesia. In FIB group only 20 (57%) patients required rescue analgesic as compared to 35 (100%) patients in PCM group.Conclusion:In FIB insertion point is away from femoral vessels and can be provided without nerve stimulator. Post-operative it is extremely crucial to provide analgesia specially initial 24 hours. FIB can provide prolong duration of analgesia, so helps in early mobilization and early rehabilitation as well as it also reduces opioid requirements. Thus, Fascia iliaca block is an effective, easy and affordable method for postoperative analgesia and can be used safely as a part of multimodal approach to pain relief after femur surgery.